Enhancing Gas Sensing Performance of TiO2-ZnO nanostructures: Effect of ZnO Concentration - Oleiwi, Dr. Hind Fadhil; Abdul Kareem, Israa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Gas sensors based on titanium dioxide (TiO2) and zinc oxide (ZnO) nanocomposites are considered energy-saving devices that are utilized to find dangerous or harmful gases in an environment. The performance of nitrogen dioxide (NO2) gas sensors have been improved by spin-coating a TiO2 and TiO2:ZnO nanocomposite with varying concentrations (90TiO2:10ZnO, 70TiO2:30ZnO, and 50TiO2:50ZnO). To correlate structural properties with gas-sensing behavior, structural and morphological characterization has been done using FESEM, XRD, and EDX.  Without any ZnO-specific crystalline phase, TiO2 X-ray diffraction was found to be indexed in the anatase crystalline structure. The ZnO is synthesized in the wurtzite phase with (002) orientation and has a smooth surface, according to the morphologies and crystalline structure of the films, which also indicated the presence of ZnO components with various crystallite sizes and lattice strains. Responses to NO2 are increased by low ZnO content. Additionally, at the average operating temperature of 250 oC, TiO2:ZnO shows a good response.